Validity of RPP based PBL in the social arithmetics - Nunung Septriani; I Made Arnawa; Ermanto Ermanto (International Conferences on Educational, Social Sciences and Technology)
Problem solving ability is one of the mathematical abilities that are important in the success of students. But the fact remains low problem solving ability. One model that can develop problem solving ability is the Problem Based Learning (PBL). RPP is one important component in learning. RPP used by teachers not specifically describe the learning process, as well as yet to be seen developing students' problem solving abilities. This study aims to determine the validity of PBL based lesson plans. The study consisted of a preliminary analysis phase, development, and assessment using the model of Plomp. However, this study is only done up to the stage of development that the validity of the stage. The instrument used in this study of guidance interviews, checklists, questionnaires, evaluation sheets and sheets validas experts themselves. The results of the validation sheet analysis showed RPP developed are valid with an average of validity index of 0.96.